REVIEW OF THE MODERN BALLASTED RAILWAY TRACKS’ SUBSTRUCTURE AND FURTHER INVESTIGATIONS - Eller, B.; Fischer, S. (Science and Transport Progress, 2019)
Purpose. The authors’ aim is to summarize the results of relevant international publications and, based on these, to give a comprehensive review about the modern ballasted tracks’ substructure. Methodology. This article is a start of a PhD research, which means it was proceeded by a secondary research. At first, the substructure and its protection layers were summarized, after that the geosynthetic cementious composite mat materials, especially the Concrete Canvas are discussed. Findings. The experiences of the geosynthetics’ and other protection layers’ functions, show that a possible using of the GCCM (geosynthetic cementious composite mat) under the ballast can be a good solution for renewing short sections in the railway tracks. Originality. One of the authors – namely Balázs Eller – is a PhD student at Szechenyi Istvan University in Gyor (Hungary). His research topic is the reinforcement possibilities of railway substructure with the usage of special (mainly cement-bonded) layers. This article was written to collect and summarize the up to date knowledge related to modern ballasted railway tracks’ substructure to be able to determine the following research ways and possibilities at this topic. The research plan will be sentenced in the near future, as well as the required laboratory and field tests will be prepared. Practical value. As expectation, after having executed the related research, the advantages and disadvantages of GCCM layers in the railway substructure will be able to defined, as well as factual deterioration process can be determined related to the ballasted tracks and their geometrical stability.